2007
DOI: 10.1017/s175173110769418x
|View full text |Cite
|
Sign up to set email alerts
|

Whole wheat versus mixed layer diet as supplementary feed to layers foraging a sequence of different forage crops

Abstract: In many cases health and welfare problems are observed in organic egg production systems, as are high environmental risks related to nutrient leaching. These disadvantages might be reduced if the layers are allowed to utilise their ability to forage to a higher degree thereby reducing the import of nutrients into the system and stimulating the hens to perform a natural behaviour. However, very little is known about the ability of modern high-producing layers to take advantage of foraging to cover their nutriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 26 publications
3
10
0
Order By: Relevance
“…Benefits of improving the efficiency of feed utilization can be extended by appropriate feeding practices: in laying hens, sequential feeding of wheat grain and protein–mineral concentrate improved feed conversion, and could facilitate the use of local feedstuffs introduced as whole grains, thus reducing feeding costs (Faruk et al , 2010). In organic egg production systems, stimulating the hens to exercise natural foraging behavior reduced the import of nutrients into the system: high-producing layers were able to forage on crops consisting of grass/clover, pea/vetch/oats, lupin and quinoa without negative effects on health or performance (egg weight and BW; Horsted and Hermansen, 2007). Geese that grazed unfertilized grass growing between tree rows in a walnut plantation increased walnut production by 26% and tree growth by 6% (Dubois et al , 2008).…”
Section: Five Principles For the Development Of Ecology-based Alternamentioning
confidence: 99%
“…Benefits of improving the efficiency of feed utilization can be extended by appropriate feeding practices: in laying hens, sequential feeding of wheat grain and protein–mineral concentrate improved feed conversion, and could facilitate the use of local feedstuffs introduced as whole grains, thus reducing feeding costs (Faruk et al , 2010). In organic egg production systems, stimulating the hens to exercise natural foraging behavior reduced the import of nutrients into the system: high-producing layers were able to forage on crops consisting of grass/clover, pea/vetch/oats, lupin and quinoa without negative effects on health or performance (egg weight and BW; Horsted and Hermansen, 2007). Geese that grazed unfertilized grass growing between tree rows in a walnut plantation increased walnut production by 26% and tree growth by 6% (Dubois et al , 2008).…”
Section: Five Principles For the Development Of Ecology-based Alternamentioning
confidence: 99%
“…This has the consequence that most hens prefer to stay in the henhouse or in the area closest to it 4, 5. However, recent studies indicate that, to a large extent, the potential contribution of nutrients to the diet from an outdoor area has been overlooked and underestimated 6, 7. These studies suggest that laying hens actually are able to cover much of their nutrient requirements from the outdoor area if abundant attractive vegetation is available.…”
Section: Introductionmentioning
confidence: 99%
“…However, it should be noted that the broilers were reared in a very extensive system, where foraging in the open-air run may contribute to the nutrition. Studies on layers in forage-based systems have shown a considerable intake of plant material, earthworms and insects, which contributed to nutrition as well as egg quality (Horsted et al, 2006;Horsted and Hermansen, 2007). In the present study, the New Hampshire was observed to be more active in the open-air run than JA757, which, in contrast, spent a lot of the time resting.…”
Section: Discussionmentioning
confidence: 39%